Strategic thinking and innovation as panaceas for hotel performance in turbulent business environments - Klenam Korbla Ledi; Rebecca Bridget Dumeda; Stephen Bandoma; Enya Ameza-Xemalordzo (Cogent Business & Management, 2024)
As the hospitality industry grapples with unprecedented crises, the relationship between innovation, strategic thinking and hotel performance during crises emerges as a critical area of exploration. The study investigates the mediating role of innovation in the relationship between strategic thinking and hotel performance during times of crisis. The study employs a quantitative approach and uses a questionnaire to solicit responses from 291 hospitality firms. Partial least squares (PLS) have been used to conduct confirmatory factor analysis (CFA) and subsequently structural equation modeling (SEM) to test the hypothesis paths of the study. The study establishes strategic thinking as a catalyst for enhanced organizational performance in the hospitality sector. The study found a positive synergy between strategic thinking and innovation, as strategic thinking catalyzes innovation, which in turn influences overall hotel performance. This synergistic relationship is essential for organizations seeking to survive and thrive in a rapidly changing business environment. The study offers practical insights for practitioners on leveraging strategic thinking and innovation synergy as a strategic tool for enhanced performance in dynamic business environments, as well as positioning themselves for long-term success and resilience.
Keywords: 650; Strategic thinking; strategic innovation; hospitality; firm performance; crises